2014
DOI: 10.1603/an13183
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and Molecular Characterization of Anastrepha Species in the spatulata Group (Diptera, Tephritidae)

Abstract: Seven species in the spatulata group were studied, namely Anastrepha alveata Stone, 1942, Anastrepha manihoti Lima, 1934, Anastrepha montei Lima, 1934, Anastrepha pickeli Lima, 1934, Anastrepha spatulata Stone, 1942, Anastrepha entodontaCanal, Uramoto & Zucchi, 2013, and AnastrephahadropickeliCanal, Uramoto & Zucchi, 2013. The molecular analysis was based on sequencing of a fragment of the cytochrome oxidase I gene and morphometric studies were based on the aculeus (traditional morphometry) and wings (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…The results of this study reveal the presence of morphometrical variants of D. citri, which are possibly determined in part by the host plant taxon as well as abiotic factors (García-Barros 1999;Bomfim et al 2011). Berlocher & Feder (2002) mention that such changes may originate as a result of the insect migration, because they have to adapt to a geographic change, a new host or both.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The results of this study reveal the presence of morphometrical variants of D. citri, which are possibly determined in part by the host plant taxon as well as abiotic factors (García-Barros 1999;Bomfim et al 2011). Berlocher & Feder (2002) mention that such changes may originate as a result of the insect migration, because they have to adapt to a geographic change, a new host or both.…”
Section: Discussionmentioning
confidence: 81%
“…For example, in Trioza erytreae Del Guercio (Moran 1968) and D. citri (Wenninger et al 2009) changes in body color have been related to differences in body mass and fecundity (Moran 1968, Wenninger et al 2009). The biological significance of the morphological variation has not been totally understood because differences of the host plant and its influence can also be attributed to abiotic factors such as temperature, humidity and precipitation (Bomfim et al 2011), photoperiod, and drought, among others (Hodkinson 2009). The fact that the morphs (polymorph variants) differ occasionally from the "normal" population type caused many to be described originally as different species (Mayr 1968).…”
mentioning
confidence: 99%
“…Hernández-Ortiz et al (2015), using linear and geometric morphometrics to analyze 40 different populations of the Anastrepha fraterculus complex in several countries (Mexico, Guatemala, Panama, Venezuela, Colombia, Ecuador and Peru), found that the flies differed in wing, ovipositor and thorax shape. Similarly, Bomfim et al (2011), also using linear and geometric morphometrics, comparing Anastrepha pickeli Lima, 1934 flies from Paraguay, Bolivia and four different states in Brazil (Bahia, Espírito Santo, Manaus and Rio Grande do Norte), showed that they differed in wing shape, wing size and ovipositor shape, suggesting that A. pickeli could also be part of a cryptic species complex, whose species were later described (Canal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Novos processos de identificação de insetos estão sendo usados como análises morfométricas e moleculares para uma identificação precisa das moscas-das-frutas do gênero Anastrepha [Bomfim et al 2011, Bomfim et al 2014. No entanto, Martineau et al [Martineau et al 2017] apontou que poucos trabalhos na literatura propuseram identificar o gênero Anastrepha através de processamento de imagem e técnicas de aprendizagem de máquina.…”
Section: Introductionunclassified